(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research affords an analysis of a strategy for implementing the Jan Merse public policy model in the PAMSIMAS program and building an ideal model as an alternative strategy for implementing a policy to improve public health service quality in Gorontalo District. It is carried out using a descriptive qualitative approach, which requires the researcher to be the key instrument. Data are collected through observation, structured interviews, documentation studies, and focus group discussions. Results demonstrate that successful policy implementation, according to Jan Merse’s approach, is affected by the aspects of information, policy content, organizational supports, community supports, and potency division, as well as skills, loyalty, and education. Based on the ground condition, it is recommended to use a TARO model approach as an alternative strategy for implementing the PAMSIMAS program policy. This model combines the government roles from the aspects of transparency, accuracy, and responsibility with the community roles from the aspect of common ownership. Accordingly, this model is expected to eliminate potential inhibitors of the program. Additionally, this model can assist the making of the roadmap of village development using the PAMSIMAS program. Eventually, the PAMSIMAS service can be delivered in a synergetic and integrated avenue and in conforming with the target to cater to the needs of people with disabilities and decrease local stunting levels.